200k views
3 votes
Find the zeros of the function: g(x)=(x -2)(3x +3)

User Yichong
by
6.4k points

2 Answers

6 votes

Answer:

x=2 x=(-1)

Step-by-step:

Solve: (x-2)(3x+3)=0

= x-2=0 3x+3=0

=x-2(+2)=0(+2) =3x-3(-3)=0(-3)

=x=2 =3x=(-3)

=3x/3=(-3)/3

=x=(-1)

User Pepsy
by
6.1k points
3 votes

Answer:

x = 2 and x = -1

Explanation:

The zeroes of the function are found by setting g(x) equal to 0:

g(x) = (x - 2)(3x + 3) = 0

By the Zero Product Property, in order for this equation to be equal to 0, each of (x - 2) or (3x + 3) or both has to equal 0. So, set each equal:

x - 2 = 0

x = 2

3x + 3 = 0

3x = -3

x = -3/3 = -1

The zeroes are thus x = 2 and x = -1.

~ an aesthetics lover

User Mfit
by
6.2k points